A life course perspective on suburbanisation - Bagyura, Márton (Sociološki pregled, 2024)
The paper explores the dynamics of migration from city to suburban area within the Budapest metropolitan area, framed within the life course approach. This approach posits that life events and prior residential experiences shape individuals’ migration decisions, with a focus on the interconnectedness of residential experiences. The results, based on semi-structured interviews, examine the motivations and expectations of new residents of the suburban area for their new residences. The main drivers of migration to suburban areas are child-rearing and the pursuit of a more favourable living environment, mirroring conditions akin to rural childhood settings. Furthermore, financial constraints and real estate prices in Budapest compared to suburban areas also emerged as significant factors.
Keywords: life course; suburbanisation; Budapest